ナンキョク チメイ メイメイ キテイ ノ カイセイ ニ ツイテ - 国立極地研究所; コクリツキョクチケンキュウショ; National Institute of Polar Research (2002)
P(論文) In the 118th general meeting of the Japanese Antarctic Research Expedition Headquarters held on 22 June 2001,a proposal to revise the Code of Antarctic Geographic Naming was discussed, and it was approved. departmental bulletin paper